Performance implications for intra-node placement of network function chains - Raumer, Daniel; Bauer, Simon; Emmerich, Paul; Carle, Georg (2017 IEEE 6th International Conference on Cloud Networking (CloudNet), 2017)
With virtual switching, a chain of virtual network functions can be realized on a single physical host. This promises higher flexibility and reduction of costs for network operators due to the usage of commodity hardware instead of expensive hardware appliances. On the down side this may cause interferences that affect the performance. Therefore, we survey the performance impact of intra-node placement of network functions. The applied metrics include throughput, latency, and CPU utilization. Our analyzed setups include Open vSwitch, Linux network namespaces, and the DPDK IP Pipeline as different chaining technologies. We introduce a model to estimate the maximum achievable throughput with respect to placement of network functions considering chaining across several computational resources.